O PROGRAMA PDE ESCOLA: UMA ANÁLISE DA SUA IMPLEMENTAÇÃO EM GUARAPUAVA - PR - Bayer, Mariana Ferreira (2012)
This study aims at analyzing the design process of the School Development Plan - SDP (Plano de Desenvolvimento da Escola - PDE Escola), as well as the enactment of such policy in State schools of Guarapuava - PR. The research was based on the policy cycle approach (BOWE et al., 1992; BALL, 1994), on the theory of policy enactment (BALL; MAGUIRE; BRAUN, 2012), and on authors whose ideas underlie the role of the State in the definition of policies (FREITAS et al., 2009; MENDES, 2006), education as a principle of social quality (CAMINI, 2001; BELLONI, 2003), and the role of school education (GIMENO SACRISTÁN, 2007; YOUNG, 2007). The study comprised: a) study on the historical, political, economical and ideological backgrounds of educational policies from the 1990s on (context of influence); b) analysis of official documents which address the organization of educational policies – SDP School, theses and dissertations on the Education Development Plan and the School Development Plan (context of text production); c) analysis of the context of practice through field research carried out in three schools in Guarapuava, involving the analysis of the Implementation Plan of each school and interviews with principals, educators and teachers. Main conclusions were as follow: a) The Federal Education Development Plan - EDP is an attempt to supply articulated actions between the Federal government, States and towns, aimed at improving the quality of public education in Brazil. However, the way it was organized it generated several manifestations among education researchers, both in favor and against it; b) The SDP School is one of the programs which compose the Federal EDP, presented as a management tool, which originated in Fernando Henrique Cardoso’s government as one of the ‘Fundescola’ developments; c) by implementing the SDP School, in Paraná State, some changes were made, aiming at making it suitable to State educational policies; d) in the context of practice, the education professionals created different strategies to implement the policy (translation and interpretation processes). Finally, it was concluded that the SDP School offers relevant contributions regarding planning according to the school reality. However it was also noticed that in the actions proposed by the schools, there is a strong influence of management perspective at different levels of proximity with a conception of democratic education.